Pengaruh Search Engine Optimization (SEO), Konten Marketing, Kualitas Produk, Perceived Value, dan Impulse Buying Terhadap Minat Beli Gen Z pada UMKM Fashion di Kota Pekalongan - Nadia Nadra Salsabila; Rini Hidayah (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
The development of digital tecnology has driven changes in consumer behavior, especially among Generation Z, in seeking information and purchasing fashion products through digital platforms. This condition requires fashion MSMEs (Micro, Small, and Medium Enterprises) to be able to implement effective digital marketing strategies to increase purchasing interest. This study aims to analyze the influence of Search Engine Optimization (SEO), content marketing, product quality, perceived value, and impulse buying on Generation Z’s purchasing interest in fashion MSMEs in Pekalongan City. The study used a quantitative approach with an explanatory research method. The sampling tecnique used simple random sampling with a total 130 Generation Z respondents who had purchased fashion MSME products through digital platforms. Data analysis was performed using multiple linier resgression with the help of IBM SPSS Statistics. The result of this study indicate that Search Engine Optimization (SEO), content marketing, product quality, perceived value, and impulse buying on Generation Z’s purchasing interest in fashion MSMEs in Pekalongan City.in addition, all independent variables simultaneously have a strong contribution in explaining consumer purchasing interest. The implications of this research show that fashion MSMEs need to optimize digital marketing strategies, improve product quality, and create creative and innovative content to be able to increase purchasing iterest in the digital era.